Mast Cell Essential Roles: Will it be a Novel Tool for Differentiating the Severity of Pediatric Appendicitis? - Poerwosusanta, Hery; Gunadi, Gunadi; Gunawan, Pricilia; Fauzi, Aditya Rifqi; Budi, Angga Setya; Poerwosusanta, Adam Rahardiyan; Esmeralda, Elvira; Aditia, Donny; Oktavianti, Ika Kustiyah; Kania, Nia; Noor, Zairin (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Appendicitis is an undesirable diagnosis, and the Alvarado score (AS) alone is insufficient in recognizing it. Many novel laboratory indicators, such as leukocytes and mast cells, differentiate. AIM: Our objective was to demonstrate that mast cells had a greater influence on appendicitis severity than the AS, neutrophils, and platelets. MATERIALS AND METHODS: An observational research in which 35 individuals with acute appendicitis at our institutions were identified for the appendix grade and allocated to one of two groups: Complicated or non-complicated. The AS and white blood cell count were calculated using the neutrophil-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), thrombocyte-to-neutrophil ratio (TNR), and total leukocyte. Mast cell count and granulation are evaluated using pathological anatomy. RESULTS: TLR could not distinguish between severe appendicitis and others, but some showed potential. NLR, TNR, total leukocyte, ASs, mast cell count, and degranulation demonstrated good sensitivity-specificity values. CONCLUSIONS: Mast cells have the potential to become a promising approach for predicting complicated pediatric appendicitis.